Mobility and Pathways to the Middle Class in Nepal - Tiwari, Sailesh; Shidiq, Akhmad Rizal; Balcazar, Carlos Felipe (World Bank, Washington, DC, 2016)
This paper introduces a variety of concepts and methods to examine living standards improvements in Nepal in a dynamic perspective. Using data from three rounds of Nepal Living Standards Surveys conducted in the past two decades, together with data from a nationally representative survey that was implemented in 2014 specifically to collect information on social and economic mobility, the paper presents novel statistics on the extent of inter- and intra-generational mobility in Nepal. The findings suggest that there has been appreciable upward mobility in education; that is, Nepalis today are increasingly more likely to be better educated than their parents. However, inter-generational mobility of occupations has been much more muted, with 47 percent of Nepal today remaining in the same occupation as their parents. Upward mobility is higher for younger cohorts and for individuals who move from their rural areas of birth to an urban area. There are also significant differences in mobility by social groups, with Dalits and Terai caste groups having lower upward mobility odds. Examining mobility within generations using synthetic panel techniques, the paper finds that: (a) for every two people who escape poverty, one slides back, suggesting significant churning around the poverty line; (b) a large fraction of those who have escaped poverty remain vulnerable to falling back, with an overall vulnerable population of 45 percent; and (c) the share of the middle class—defined as those with sufficiently low likelihood of falling back into poverty—has increased steadily over the past two decades, reaching 22 percent in 2010–11. However, triangulating subjective well-being data from Gallup, it appears that a majority of even those who constitute the middle class are fundamentally insecure about their economic futures. The prevalence of a large vulnerable population and a nascent, growing but struggling middle class represents a key challenge to consolidating recent gains in moving people out of poverty.